A concepção freiriana de linguagem e sua centralidade na alfabetização de jovens e adultos - Beltrame, Marisete Tramontina (2024)
This dissertation's theme is Youth and Adult Education, looking especially at the role that language plays in this type of education. The guiding question to guide the research is formulated as follows: what is the conception of language that supports/substantiates the possibility of authentic, not merely mechanical, learning of reading and writing by young people and adults who are not literate at the right age? The general objective of the study is to highlight the way in which language understanding impacts the teaching of reading and writing in young people and adults. As specific objectives, we seek to: 1) identify historical aspects of Youth and Adult Education in Brazil and distinguish the different mechanisms that involve learning to read and write for young people and adults, highlighting how in EJA the teaching of reading should seek a deep overlap between text and context; 2) address the perception constructed between text and context in literacy, based on Paulo Freire's pedagogy; 3) show which understanding of language, from a Freirean perspective, is adequate to support/substantiate the possibility of critical literacy and not just as a mechanical assimilation of reading and writing by young people and adults. The research has a predominantly bibliographical character, focusing on the interpretation of the works of Freire and commentators. Freire's main texts studied are Pedagogy of the Oppressed, Pedagogy of Autonomy and Education as a practice of Freedom. The work is divided into three chapters. In the first, a historical review of writing and the ability to read and write is made, with the intention of showing the maturing understanding that in today's society literacy is not a privilege, but people's right and necessity. The second chapter delves into Paulo Freire's pedagogy, focusing more specifically on identifying the understanding of language that accompanies his adult literacy method. Finally, in the third chapter, an approach to the Freirean conception of language that underpins critical literacy is developed. It is shown that in such a conception of language, the importance of students learning to say their own words through dialogue stands out as an ethical and literacy principle. In terms of the result of this journey, we obtained the understanding that, in Freire's conception, language presents itself as a generator, rooted in the world of students, and that it is constituted through the reading of this world, in addition to becoming determinant for the success of literacy understood in its critical sense and mobilizing transformations.